2015
DOI: 10.1123/jsr.2014-0191
|View full text |Cite
|
Sign up to set email alerts
|

Gastrocnemius Stretching Program: More Effective in Increasing Ankle/Rear-Foot Dorsiflexion When Subtalar Joint Positioned in Pronation Than in Supination

Abstract: After a 3-wk gastrocnemius-stretching program, when measuring dorsiflexion with the STJ positioned in supination, the participants who completed a 3-wk gastrocnemius stretching program with the STJ positioned in pronation showed more increased dorsiflexion at the ankle/rear foot than participants who completed the stretching program with the STJ positioned in supination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the present study, ankle stiffness was a risk factor for ankle sprain. Johanson et al suggested that subtalar joint supination has a close relationship with limitations in ankle dorsiflexion 10 ) . Edo et al reported that supinated subtalar joint causes lateral loading of body weight on the foot, which is a risk factor for inversion ankle sprain.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ankle stiffness was a risk factor for ankle sprain. Johanson et al suggested that subtalar joint supination has a close relationship with limitations in ankle dorsiflexion 10 ) . Edo et al reported that supinated subtalar joint causes lateral loading of body weight on the foot, which is a risk factor for inversion ankle sprain.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle brace was advised for 2 weeks for improving the stability at the ankle joint [7] From the first day of physical therapy treatment, cryotherapy with cold packs for 20 minutes was given [5] . Ultrasound with phonophoresis to the lateral aspect of the ankle below the lateral malleoli was given for 7 min with the intensity of 0.8 mW/cm2.…”
Section: Week 1-2-(early Post-immobilization Phase)mentioning
confidence: 99%